2020
DOI: 10.1038/s41415-020-2178-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimum intervention oral healthcare for people with dental phobia: a patient management pathway

Abstract: Dental phobia is relatively common among adults and often associated with poorer oral health as a consequence of delaying dental treatment until advanced disease has caused intolerable symptoms. The increased rates of active disease may also have an impact on oral health-related quality of life (OHR QoL). Minimum intervention oral healthcare (MIOC) combines four key domains: detection and diagnosis, prevention and control of oral disease, minimally invasive (MI) operative interventions and review/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Mark (2017) concluded that some methods, such as adapting to body posture and relaxation, can reduce dental anxiety (24). Heidari et al (2020) also reported a relationship between anxiety and unpleasant experience before dental appointment (27).…”
Section: Discussionmentioning
confidence: 99%
“…Mark (2017) concluded that some methods, such as adapting to body posture and relaxation, can reduce dental anxiety (24). Heidari et al (2020) also reported a relationship between anxiety and unpleasant experience before dental appointment (27).…”
Section: Discussionmentioning
confidence: 99%
“…Following the same concept, VR can serve as an effective non-pharmacologic analgesic for dental pain [45]. Several studies reported that VR reduced their awareness of dental pain and that they were so absorbed in the VR that they did not think often about their pain [46][47][48]. The patient's inability to see the dental practitioner and instruments may be one advantage of VR.…”
Section: Applications In Dental Phobiamentioning
confidence: 99%
“…Non-pharmacological behavioural management techniques can include simple strategies such as rapport building, enhancing sense of control, cognitive distraction, systematic desensitisation, and provision of procedural, sensory and coping information. [21][22][23] The use of cognitive behavioural therapy (CBT) is a well-established therapy for people with dental anxiety, and has a wide base of evidence for efficacy and effectiveness, maintaining positive effects over time. 22,24,25 Once sedation assessment has been undertaken, and the sedation technique has been decided upon, the justification for this should be documented in the patient's notes.…”
Section: Patient Assessmentmentioning
confidence: 99%
“…A high BmI can result in increased risk of sedation-related complications due to increased adipose tissue surrounding the airway leading to reduced patency, increased metabolic demands, associated comorbidities and increased challenges in managing the airway should complications arise. 21…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%